Generalized Duality and Integrability - Epstein, Larry G. (Econometrica, 1981)
[The theory of duality has been an extremely useful tool in the analysis of the standard models of consumer and producer behavior. This paper describes an extension of the theory to a wider class of problems of static optimization. The generalized duality theory is then applied to the integrability question in fairly general optimization models. A major gap in the comparative statics of optimization models is partially closed.]